Поиск производных ингибиторов протеинфосфатаз, потенциально связанных с регуляцией цитоскелета растений - Самофалова, Д.А.; Карпов, П.А.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. Okadaic acid (OA) strongly inhibits protein serine/threonine phosphatases PP1 and PP2A/2B. In comparison with the other inhibitors the inhibitory effect of OA is strongest for PP2A, followed by PP1, and then PP2B. This toxin is now used as powerful research tool of an increasingly wide variety of cellular events regulated by reversible protein phosphorylation. Because of the lack of highly PP1 and PP2A/2B selective inhibitors, design and search of new biologically active OA derivatives is extremely important. Methods. Modeling of PP1 and PP2A spatial structures were performed using SWISS-MODEL server. The ligands for molecular docking were prepared using CCDC Hermes molecular editor. Flexible docking of OA derivatives was performed using CCDC GOLD Suite 5.1. Binding site for PP1 was specified in 15 Е radius about -NE2 (HIS125), PP2А in 20 Е radius about -ND2 (ASN117), and for РР4 in 15 Е radius about - ND1 (ARG129). For docking evaluations, CCDC GOLD scoring functions (ChemScore, GoldScore and ASP) were used. Finally, docking results were evaluated by molecular dynamics simulations in GROMACS. Results. Using template based modeling and human structures of PP1 (PDB: 1U32) and PP2A (PDB: 2IE4) in complex with okadaic acid 3D-models of plant homologues from Arabidopsis thaliana, Emericella nidulans and Salmonella typhimurium were build. A high level of sequence and structure identity in plant and animal phosphatases allow us to conclude similarity of OA binding sites in PP1, PP2A and PP4. Based on chemoinformatic analysis using PubChem (http://pubchem.ncbi.nlm.nih. gov) and ZINK (http://zinc.docking.org/) databases, 26 OA-derivatives of were selected. Complexes with selected ligand were predicted by results of flexible docking and evaluated by docking scoring functions and MD results. Conclusions. As a result, five compounds not previously described as PP1, PP2A and PP4 inhibitors, were selected.